Efektifitas Pemberian Pudding Zhanthorhiza Terhadap Perubahan Berat Badan Pada Anak Stunting Di Wilayah Kerja Puskesmas Benteng - Rina Limidina; Burhanuddin Basri; Eva Martini (Pusat Riset dan Inovasi Nasional, 2024)
Background: Stunting is a child under five years of age (toddlers) whose growth is disrupted due to chronic nutritional deficiencies, and results in the child having a short body. Stunting has a very broad impact, including on individuals, families, communities and countries. Stunting which has an individual impact will cause disruption of brain growth which can result in permanent impairment of brain function. Children with stunting will experience difficulties in learning because they have poor motor skills. The risk is higher for people with stunting, namely chronic diseases in adulthood. Temulawak can also be an attractive food for everyone, namely by processing it into pudding. Pudding is usually used as a dessert which has a sweet taste and attractive appearance. When making this pudding, ginger is added which has the function of increasing appetite. Apart from that, the curcumin content in ginger can give the pudding a yellow color which can beautify the appearance of the pudding. Objective: To determine the effectiveness of giving zanthorhiza pudding on weight changes in stunted children. Method: The design in this research uses Quasi-experiment using a one group pretest posttest design approach, the final sample size required in this research is 18 respondents, the sampling technique uses purposive sampling, and data analysis uses the Paired Samples Test. Results: based on the results of statistical tests using the Paired Samples Test, the resulting P value was 0.000 < 0.05, where it can be concluded that there is an effect of giving Zanthorhiza pudding on weight changes in stunted children. Conclusion: there is an effect of giving Zanthorhiza pudding on weight changes body weight in stunted children. Suggestion: It is hoped that the results of this research can be an innovation for parents at home to provide Zanthorhiza pudding as an alternative to increase children's appetite and increase the body weight of stunted children.